Pulmonary Toxicity of Long, Thick MWCNT and Very Long, Thin Carboxylated MWCNT Aerosols Following 28 Days Whole-Body Exposure - Chang Guo; Matthew D. Wright; Alison Buckley; Adam Laycock; Trine Berthing; Ulla Vogel; Frédéric Cosnier; Laurent Gaté; Martin O. Leonard; Rachel Smith (Toxics)
Pulmonary exposure to carbon nanotubes (CNTs) has been linked to a series of adverse respiratory effects in animal models, including inflammation, genotoxicity, fibrosis, and granuloma formation, the degree and characteristics of which are considered dependent upon the detailed physicochemical properties of the material as inhaled. To further explore the effect of variations in physicochemical properties on pulmonary effects, two different multi-walled CNTs (MWCNTs) were tested in vivo: a pristine MWCNT (pMWCNT) (NM-401) and a surface-modified MWCNT (MWCNT-COOH). Female Sprague–Dawley rats were whole-body exposed for 28 days to MWCNT aerosols (pMWCNT (0.5 and 1.5 mg/m3) and MWCNT-COOH (1.5 and 4.5 mg/m3)) and followed up to 1 year post-exposure. The inhalation exposures resulted in relatively low estimated lung deposition. Bronchoalveolar lavage fluid (BALF) analysis indicated inflammation levels broadly consistent with deposited dose levels. Lung histopathology indicated that both MWCNTs produced very limited toxicological effects; however, global mRNA expression levels in lung tissue and BALF cytokines indicated different characteristics for the two MWCNTs. For example, pMWCNT but not MWCNT-COOH exposure induced osteopontin production, suggestive of potential pre-fibrosis/fibrosis effects linked to the higher aspect ratio aerosol particles. This is of concern as brightfield and enhanced darkfield microscopy indicated the persistence of pMWCNT fibres in lung tissue.